Prescribing Inertia or Not? Quantitative Investigation of Loop Diuretics Prescribing after Palliative Care Consultation among Patients with Heart Failure - Zhang, Zidong; Frick, William; Hinyard, Leslie; Subramaniam, Divya S (Journal of Cardiology and Cardiovascular Medicine, 2024)
Purpose: Loop Diuretics (LD) are the first-line pharmacotherapy to address Heart Failure (HF)-associated edema and dyspnea. However, LD causes frequent urinary, resulting in inconvenience and possibly undermining the quality of life. While prescription adjustment is an essential part of Palliative Care Consultation (PCC), it remains unclear how PCC affects the deprescribing of diuretics for adults with HF. Methods: We conducted a pre-post analysis of the percentage of HF patients who were prescribed LD in a national Electronic Health Record (EHR) database 12 months before and after the first PCC. The difference in prescription rates between the periods was determined. Adjusted associations of post-PCC LD prescription with pre-PCC LD prescription and patient’s characteristics, insurance, provider type, and clinical factors were quantified. Results: From 2010 to 2018, 5,969 patients with newly diagnosed HF received at least one PCC, among whom 2,539 (42.5%) were prescribed LD before and 1,552 (26.0%) after their first PCC. Despite a decrease in LD prescription rate encompassing the date of PCC, post-PCC LD prescribing was strongly associated with pre-PCC prescribing (aOR[95%CI] 3.2[2.8,3.7]) and varied by age at first PCC, year of HF diagnosis (aOR[95%CI] 2.1[1.9,2.4]) and months from HF diagnosis to first PCC. While our finding demonstrates reduced polypharmacy associated with PCC, the strong association between pre- and post-PCC indicates reverse therapeutic inertia. Future research should investigate the benefits and costs of polypharmacy among specific patient groups to help develop personalized treatment for HF.